2010
DOI: 10.3899/jrheum.100461
|View full text |Cite
|
Sign up to set email alerts
|

Incident Comorbidity Among Patients with Rheumatoid Arthritis Treated or Not with Low-dose Glucocorticoids: A Retrospective Study

Abstract: Patients with RA treated with low-dose GC compared to patients never treated with GC show a higher prevalence of fractures, arterial hypertension, myocardial infarction, and serious infections, especially after 5 years of GC treatment. The high prevalence of myocardial infarction and fractures in patients with RA suggests that a more accurate identification of risk factors and prevention measures should be adopted when longterm GC treatment is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…Indeed, longterm GC therapy was associated with the development of arterial hypertension in our study 4 , and undoubtedly this can predispose to cardiovascular diseases. Similar results were found in rheumatoid arthritis 5 . There are probably only 2 ways to reduce the risk of GC-related cardiovascular adverse events: first, to shorten the GC duration/cumulative dose whenever possible, not relying on the safety of low-dose GC; and second, to strictly monitor arterial pressure and protect the cardiovascular system with the available prevention strategies.…”
Section: To the Editorsupporting
confidence: 89%
“…Indeed, longterm GC therapy was associated with the development of arterial hypertension in our study 4 , and undoubtedly this can predispose to cardiovascular diseases. Similar results were found in rheumatoid arthritis 5 . There are probably only 2 ways to reduce the risk of GC-related cardiovascular adverse events: first, to shorten the GC duration/cumulative dose whenever possible, not relying on the safety of low-dose GC; and second, to strictly monitor arterial pressure and protect the cardiovascular system with the available prevention strategies.…”
Section: To the Editorsupporting
confidence: 89%
“…In contrast to the RCTs which showed no association between GC use and all cataracts (RD 0.01, 95%CI -0.01–0.03), an association was observed in the observational cohort studies [2226], with a estimated risk difference of 0.07, 95%CI 0.04–0.10. The RCT and observational literature regarding glaucoma was particularly limited as was that addressing the effect of dose and duration of GC therapy.…”
Section: Discussioncontrasting
confidence: 66%
“…They found that both cataract and glaucoma fit the threshold pattern with a threshold dose of 5mg per day for cataract and 7.5mg per day for glaucoma in patients on GCs for more than 6 months. Mazzantini et al [26] did not find any difference in cataract prevalence between those treated with GCs for <2 years, 2–5 years or >5years.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The task force debated whether there was a safe lower level of glucocorticoid dosing. While this question has been studied in other diseases where no such safe lower level could be identified,96 97 there are no studies specifically addressing this issue in SLE. Nonetheless, based on the available evidence and general pharmacological considerations, the task force supported the main recommendation to aim for the lowest glucocorticoid dosage during maintenance treatment, and the comment to withdraw glucocorticoids completely ‘if possible’.…”
Section: Resultsmentioning
confidence: 99%